THE EFFORTS TO INCREASE MULTIPLICATION LEARNING OUTCOMES WITH QUANTUM LEARNING MODEL - Awaludin, Muhamad; Suryani, Yeyen; Riyadi, Mohamad (Universitas Kuningan, 2019)
This study aims to improve Mathematics learning outcomes with quantum learning models on multiplication material in class III B SDN 1 Purwawinangun Kuningan. The type of this study is Classroom Action Research (CAR) by Kemmis and Mc. Taggart models consisting of 2 cycles. Each cycle is carried out with four main activities, namely planning, implementing, observing, and reflecting by using quantum learning model. The results of this study indicate enhancement in Mathematics learning outcomes. In the cycle I, the completeness percentage of students learning outcomes are 68% with an average students learning outcomes are 70.2. Meanwhile, in cycle II a percentage of students learning outcomes are 92% with an average learning outcomes are 83.3. From the action research, it can be concluded that by using the quantum learning model can improve the results of Mathematics learning outcomes of students in class III B SDN 1 Purwawinangun, especially in Multiplication material.